Answer:
In an arithmetic sequence, the difference between any consecutive terms should be always the same, then we have:
(y + 3) - (y + 2) = D
(2*y^2 + 1) - (y + 3) = D.
From the first equation, we can find the value of D:
y + 3 - y - 2 = D
1 = D.
Replacing this in the second equation, we have:
(2*y^2 + 1) - (y + 3) = 1
Now we can solve this equation:
2*y^2 + 1 - y - 3 - 1 = 0
2*y^2 - y - 3 = 0.
The solutions of this quadratic equation can be found with the Bhaskara's equation:
[tex]y = \frac{1 +- \sqrt{1^2 - 4*2*(-3)} }{2*2} = \frac{1+-\sqrt{25} }{4} = \frac{1+-5}{4}[/tex]
Then the possible values of y are:
y = (1 + 5)/4 = 6/4
y = (1 - 5)/4 = -1